Optimizing Mosque-Based Cash Waqf for Real Sector Empowerment: Evidence from Medan, Indonesia - Iqbal, M.; Nasution, Muhammad Syukri Albani; Nasution, Yenni Samri Juliati (El-Qist: Journal of Islamic Economics and Business (JIEB), 2025)
This study examines how Mosques in Medan manage waqf funds to support productive, empowering economic programs for the ummah. Using a qualitative case study approach, data were collected through in-depth interviews with mosque administrators, waqf practitioners, and related stakeholders, and analyzed using NVivo 12 to identify patterns, themes, and Mosque typologies in cash waqf management. The findings reveal that while many mosques in Medan have initiated cash waqf collection, few have successfully channeled these funds into sustainable economic empowerment initiatives. Key determinants of effective management include institutional structure, congregational engagement, collaboration with Islamic financial institutions, and digital support. Theoretically, this study contributes to the development of an integrative framework that positions mosques as socio-economic institutions within the broader discourse of Islamic economics. This study contributes to Islamic social finance literature by formalizing mosque typology as an institutional variable, thereby strengthening the conceptual link between mosque governance and economic empowerment. Practically, it proposes a typology-based Mosque replication model to enhance the sustainability and scalability of cash waqf-driven economic empowerment. This integrative approach offers a pathway for transforming mosques into centers of community-based economic justice and prosperity.